Transcriptional analysis and promoter characterization of two differentially expressed outer membrane protein genes of Ehrlichia chaffeensis - Peddireddi, Lalitha (Kansas State University, 2009)
Ehrlichia chaffeensis is a Gram negative, rickettsial organism responsible for human monocytic ehrlichiosis, an emerging disease in people. E. chaffeensis infection to a vertebrate host occurs when the pathogen is inoculated by an infected tick, Amblyomma americanum. White-tailed deer is a reservoir host for this pathogen. The strategies employed by E. chaffeensis in support of its dual host adaptation and persistence are not clear. One of the possible mechanisms by which the pathogen adapts and persists, is by altering its gene expression in response to its host cell environments. Recently, we reported that E. chaffeensis protein expression including that from a 28 kDa outer membrane protein multigene locus (p28-Omp), is influenced by macrophage and tick cell environments. E. chaffeensis expresses p28-Omp gene 14 product predominantly when it is grown in tick cells and p28-Omp gene 19 protein in macrophages. We hypothesize that E. chaffeensis achieves its host-specific gene expression by employing transcriptional regulation by sensing the host cell signals. In support of this hypothesis, transcriptional analysis of 14 and 19 genes was performed utilizing several RNA analysis methods. The results supported our hypothesis that the gene regulation occurs at mRNA level in a host cell-specific manner. This analysis also identified transcription start sites and located putative promoters for the p28-Omp genes 14 and 19. Promoter regions of genes 14 and 19 were mapped to identify gene-specific differences, RNA polymerase binding sequences and the putative regulatory elements that may influence the promoter activities. Electrophoretic mobility shift assays revealed interaction of E. chaffeensis proteins with gene 14 and 19 promoters. Several E. chaffeensis putative regulatory proteins were expressed as recombinants and their effects on a p28-Omp gene promoter activity were evaluated. In summary, we demonstrated that the differences in the E. chaffeensis p28-Omp genes 14 and 19 are the result of their regulation at transcriptional level in response to the host cell environment. We also identified RNA polymerase binding regions and several DNA sequences that influenced promoter activity. This is the first description of a transcriptional machinery of E. chaffeensis. The data from these studies provide important insights about molecular mechanisms of gene regulation in E. chaffeensis.
Keywords: Ehrlichia chaffeensis; transcription; outermembrane protein genes; promoter; Biology, Microbiology (0410); Biology, Molecular (0307)